Project-level accessibility analysis for land-use planning. (January 2017) - Levine, Jonathan; Merlin, Louis; Grengs, Joe
Abstract: The concept of accessibility has made inroads into planning practice, largely at the system level. That is, accessibility is measured or modeled for current or future regional transportation and land-use scenarios for evaluation or broad policy guidance. Yet system-level scenarios cannot readily be applied to the project-by-project decision-making that characterizes the majority of transportation and land-use planning decisions. Accessibility evaluation of individual transportation or land-development projects differs from system-level analysis in essential ways and thus requires specialized tools. This article proposes an elasticity-based metric of accessibility that can enable project-level evaluation of land-development projects as an accessibility-based alternative to traffic-impact analysis. The metric is demonstrated for three projects in Ann Arbor, Michigan, USA. The metric is shown to be sensitive to the location of development and capable of distinguishing among the analyzed projects in accessibility terms. Where mobility-based evaluation tends to rank peripheral development highly, the proposed accessibility metric appropriately rates central development as contributing the most to regional accessibility even after accounting for the traffic delay it engenders. Highlights: Land-use projects can be evaluated using an accessibility-elasticity indicator that incorporates the results of standard traffic-impact analyses. This approach solves two principal problems attending the accessibility evaluation of land-use projects. The indicator is designed to be used by land-use and transportation planners in local practice. The indicator is sensitive to project location, and—unlike highway level-of-service—does not disadvantage development in central locations.